Progressive Supranuclear Palsy—Parkinsonism Predominant (PSP-P)—A Clinical Challenge at the Boundaries of PSP and Parkinson's Disease (PD) - Alster, Piotr; Madetko, Natalia; Koziorowski, Dariusz; Friedman, Andrzej (Frontiers in Neurology, 2020)
Progressive Supranuclear Palsy (PSP) and Parkinson’s Disease (PD), especially in their early stages, show overlapping clinical manifestations. The criteria for the diagnosis of PSP, released in 2017, indicate four basic features of the disease – postural instability (P), akinesia (A), oculomotor dysfunction (O) and cognitive and lingual disorders (C), which clarify the interpretation of the disease. There is growing interest in the second most common variant of PSP – parkinsonism predominant PSP-P. It is observed in up to 35% of cases. The diagnosis of PSP-P requires the presence of akinetic-rigid predominantly axial and levodopa resistant parkinsonism (A2) or parkinsonism with tremor and/or asymmetric and/or levodopa responsive (A3). The development of supplementary methods of examination added new insights to observations related to PSP-P. Among the methods recently analyzed are freezing of swallowing and speech breathing assessment, transcranial sonography, and various methods using magnetic resonance imaging, such as pons/midbrain area ratio and magnetic resonance parkinsonism index (MRPI), fractional anisotropy or mean diffusivity. The proper examination of overlapping parkinsonian syndromes, regardless of the development of the method of examination, remains an incompletely explored issue. The aim of this review is to elucidate which factors may be interpreted as influential in the differential diagnosis of PSP-P, PSP-RS and postural instability and gait difficulty (PIGD) subtype of Parkinson’s disease (PD).